Service Information System Animal Product Testing at Bogor's Quality Testing & Certification Center for Animal Products (BPMSPH) - Sandra Jamu Kuryanti; Siti Nur Khasanah; Eko Yulianto (Institute of Computer Science (IOCS), 2021)
The Bogor Animal Product Quality & Certification Testing Center (BPMSPH) in carrying out the testing service process still uses the system of meeting directly with service users to carry out tests and use paper media for recording service user data. Services and data processing like this require considerable effort and time, the risk of damage to paper as a medium for recording service user data is also a problem. Therefore, a web-based animal product testing service information system design was made at the Bogor Animal Product Quality & Certification Testing Center (BPMSPH) which uses the waterfall model as a software development method and the data collection techniques used consist of observations, interviews and literature studies. This designed system provides online testing services where service users can fill out test forms anywhere without having to go directly to BPMSPH. Hopefully this web-based testing service system can make it easier for service users to carry out tests at the Bogor Animal Product Quality & Certification Testing Center (BPMSPH).